2011
DOI: 10.1097/mbc.0b013e32834512f4
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism in patients with pancreatic cancer: implications of circulating tissue factor

Abstract: Among cancers, pancreatic cancer is known to be associated with a higher incidence of venous thromboembolism (VTE). The aim of the study was to determine the implication of circulating tissue factor (TF) in VTE related to active pancreatic cancer. One hundred and sixty-four consecutive patients who participated to the Etude des Determinants et Interactions de la Thrombose veineuse (EDITH) study between January 2005 and August 2007 for symptomatic VTE related to active pancreatic cancer (n = 8), active cancer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
(39 reference statements)
1
11
0
Order By: Relevance
“…However, a study investigating VTE in cancer patients found higher median levels of circulating TF in patients with pancreatic cancer (12.67 pM, range 0.05–112.04 pM) than in those with other cancers (2.01 pM, range 0.05–43.92 pM). 12 Of note, these experimental values are within the range of the calculated threshold pro-thrombotic concentrations for circulating TF estimated by our numerical model under simulated venous conditions.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…However, a study investigating VTE in cancer patients found higher median levels of circulating TF in patients with pancreatic cancer (12.67 pM, range 0.05–112.04 pM) than in those with other cancers (2.01 pM, range 0.05–43.92 pM). 12 Of note, these experimental values are within the range of the calculated threshold pro-thrombotic concentrations for circulating TF estimated by our numerical model under simulated venous conditions.…”
Section: Discussionsupporting
confidence: 78%
“…10,14,52 While there is evidence of correlation between circulating TF and thromboembolism, the mechanistic role of circulating TF remains incompletely defined. 12,30,51 In vivo studies using a photochemical carotid artery injury model and inferior vena cava ligation suggest that TF-bearing leukocytes have little impact on thrombus formation, implying that surface-bound TF along the vessel wall drives thrombosis. 11 Alternatively, laser induced injury models provide evidence that both blood-borne and surface-bound TF are involved in initiating and propagating thrombosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreatic cancer (PaCa) is associated with high incidence of venous thromboembolism (VTE) [27,28,29], which suggests a close interplay between PaCa cells and platelets, the latter being a key player in haemostasis and thrombosis [30,31]. VTE in cancer is associated with a low survival rate [32].…”
Section: Discussionmentioning
confidence: 99%
“…These molecules include thrombomodulin, 34 thrombin, 35 thrombin-antithrombin III complex, 36 plasminogen activator inhibitor-1, 37 platelet factor 4, 38 P-selectin glycoprotein ligand 1, 39 fibrin, 40 and tissue factor pathway inhibitor, 41 with the most attention focused on the role of tissue factor 42 (both soluble and cell membrane-bound 36 ) in pancreas carcinogenesis, and related thrombogenicity. Delluc et al 43 observed higher levels of tissue factor in patients with pancreas cancer and thrombosis than in those with non-pancreas cancers and thrombosis or with idiopathic thrombosis.…”
Section: Pancreas-specific Molecular Risk Factors For Thrombosismentioning
confidence: 98%